Kesan Faktor Terminologi, Semantik Dan 'Urf Dalam Penghuraian Berkaitan Isu Makanan - Zainur Rijal Abdul Razak; Wan Azura Wan Ahmad; Arnida A. Bakar; Lubna Abdul Rahman (Universiti Malaya, 2024)
How to Cite Abdul Razak, Z. R., Wan Ahmad, W. A., Abdul Rahman, L., & Abu Bakar, A. (2014). Kesan Faktor Terminologi, Semantik dan ’Urf dalam Penghuraian Berkaitan Isu Makanan. Jurnal Fiqh, 11, 119–140. https://doi.org/10.22452/fiqh.vol11no1.6